Small Bowel Capsule Endoscopy: Benefits of Rereading Rather than Repeating—A Single Blinded Randomized Study - AlAyoubi, Alamir-Noureddine; Tabcheh, Ayman; Obeid, Nourhane; Challita, Antoine; Matta, Judy; Farhat, Said (Journal of Digestive Endoscopy, 2023)
Objectives Small bowel capsule endoscopy (SBCE) technology detects small bowel lesions. Many factors affect its sensitivity. SBCE is also costly, and patients might not be able to repeat the test when results are equivocal. Instead of repeating the test, reading the results by two endoscopists might provide a better or a cheaper option in the right settings. We studied the sensitivity of SBCE when read by two different physicians and checked if, rather than repeating the examination, rereading the results improved its sensitivity. Furthermore, we studied the effect of small bowel transit time (SBTT) on the diagnostic yield.Materials and Methods A retrospective cohort study on capsule endoscopies was conducted between 2018 and 2019 in a tertiary care center in Lebanon. A total of 42 patients with anemia or obscure gastrointestinal bleed were included for SBCE after a negative evaluation with upper and lower gastrointestinal (GI) endoscopy. Two specialists read the results. The second physician was blinded from the first reader's results. We compared the sensitivity of the two readings. SBTT correlation with the diagnostic yield was calculated.Results Out of 42 patients, 18 tested positive in the first reading and 31 in the second reading. The diagnostic yield increased from 43 to 74% (p = 0.0043). Among the 33 patients who had a documented SBTT, longer SBTT correlated with a higher diagnostic yield (odds ratio [OR] > 1), but no statistical significance was demonstrated.Conclusion Within the limitations of this study, we found that rereading capsule endoscopy can be more cost-effective than repeating the test.
Keywords: capsule endoscopy; small bowel transit time; anemia; obscure gastrointestinal bleed